The effect of diesel pilot injection strategy on combustion and emission characteristic of diesel/methanol dual fuel engine. (15th September 2022) - Tao, Wenhui; Sun, Tao; Guo, Wenjun; Lu, Kangbo; Shi, Lei; Lin, He
Highlights: Effects of pilot injection timing and pilot mass percent are investigated. Advanced PIT and high pilot mass percent can increase the thermal efficiency. The combustion mode can decrease the NOx and smoke emission simultaneously. Abstract: The effects of diesel fuel pilot injection timing, pilot mass percent and methanol substitution rate on the combustion and emissions of a diesel-methanol dual fuel engine were experimentally investigated. The experiments were conducted on a single-cylinder, naturally aspirated common rail diesel engine modified with a methanol injection system. The results indicated that the addition of pilot injection advanced the ignition time and increased the heat release rate. With the advancement of pilot injection timing, the ignition delay increased, and the indicated thermal efficiency reduced. The NOx emission first decreased and then increased while the smoke emission showed the opposite trend. With the increase in the pilot mass percent, the peak in-cylinder pressure and the heat release rate increased. Meanwhile, the ignition time and the CA50 advanced. At different pilot injection timing, the combustion duration and the indicated thermal efficiency showed different trends. Meanwhile, with the increase in the pilot mass percent, the NOx emission increased and the smoke emission decreased. When the MSR increases from 20% to 40%, the indicated thermal efficiency increases by 1.9 percentage points, and the NOx and smoke emissions decrease by 88% and 61% respectively by advancing the PIT and increasing the pilot mass percent with the EGR combined. It can be concluded that, at high MSR, advancing the pilot injection timing and increasing the pilot mass percent with EGR combined is a better injection strategy to improve the performance of combustion and emissions.